Quantum-trajectory Monte Carlo method for study of electron–crystal interaction in STEM. Issue 27 (21st July 2015) - Ruan, Z.; Zeng, R. G.; Ming, Y.; Zhang, M.; Da, B.; Mao, S. F.; Ding, Z. J.
<x xml:space="preserve">Abstract</x> A quantum trajectory Monte Carlo method is developed to simulate electron scattering and secondary electron cascade process in crystalline specimen.